ANALISIS USABILITY USER INTERFACE MENGGUNAKAN METODE USABILITY METRIK PADA APLIKASI VIRCLE - Hosana, Vionita; Mohammad Sofyan S. Thayf; Renny, Renny (KHARISMA Tech, 2024)
This research aims to analyze the usability of the user interface in the VirCle application using the usability metric method. Data were collected through observation testing, questionnaires, and interviews. The research results indicate problems in task success, particularly in the photo uploading process that requires a description before posting. Although some users exceeded the predetermined time in the time on task, the overall required time is relatively short. The error rate is low, only around 4%. The System Usability Scale (SUS) questionnaire results show an average score of 75, which falls into the "Good" category. The interview results obtained positive user responses, although some problems were identified. Overall, the VirCle application has good potential and usability, with some improvements needed, especially regarding photo description filling and toolbar icons. This research is expected to contribute to application developers in improving the usability of VirCle and providing a better user experience.